2015
DOI: 10.1016/j.rbo.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Luxação acromioclavicular: tratamento e reabilitação. Perspectivas e tendências atuais do ortopedista brasileiro

Abstract: Como citar este artigo: Arliani GG, et al. Luxação acromioclavicular: tratamento e reabilitação. Perspectivas e tendências atuais do ortopedista brasileiro. Rev Bras Ortop. 2015. http://dx.doi.org/10.1016/j.rbo.2014.09.013 ARTICLE IN PRESS RBO-932; No. of Pages 8 r e v b r a s o r t o p . 2 0 1 5;x x x(x x):xxx-xxx w w w . r b o . o r g . b r Artigo original Luxação acromioclavicular: tratamento e reabilitação. Perspectivas e tendências atuais do ortopedista brasileiro ଝ informações sobre o artigo Histórico do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Dezenas de tratamentos cirúrgicos já foram propostos, mas atualmente ainda não existe um padrão-ouro. 11 Essa variedade de técnicas envolve: amarraias subcoracoide com fios de alta resistência, transferência do ligamento coracoacromial (técnica de Weaver-Dunn), reconstrução dos ligamentos acromioclavicular e coracocavicular com enxertos. Fixação clavicular-coracóide com parafuso (técnica de Bosworth), âncoras de sutura e uso de endobutton.…”
Section: Introductionunclassified
“…Dezenas de tratamentos cirúrgicos já foram propostos, mas atualmente ainda não existe um padrão-ouro. 11 Essa variedade de técnicas envolve: amarraias subcoracoide com fios de alta resistência, transferência do ligamento coracoacromial (técnica de Weaver-Dunn), reconstrução dos ligamentos acromioclavicular e coracocavicular com enxertos. Fixação clavicular-coracóide com parafuso (técnica de Bosworth), âncoras de sutura e uso de endobutton.…”
Section: Introductionunclassified
“…Superoinferior stability is maintained by the coracoclavicular (CC), trapezoid and conoid ligaments. 1 Fukuda et al, 2 identified that the AC ligaments were the main limiting factors for posterior and superior translation in minor dislocations. In larger dislocations, the conoid ligament is the primary limiting factor for upper translation, while the trapezoidal ligament provides tensile strength to the AC joint.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Most authors recommend the non-surgical treatment for type-I and type-II injuries. 1,8,9 The treatment for type-III lesions is controversial, since several authors have presented conservatively-treated case series with good to excellent outcomes. 10,11 However, other authors have reported cases with pain and other residual symptoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation